PEMBELAJARAN TEMARIK-EKSPLORATIF-DEMOKRATIK (TED) BERTEMAKAN PERMAINAN TRADISIONAL CENGE-CENGE BAGI MAHASISWA JURUSAN FISIKA - Moningkey, Kirsty Diva Laurentsia; Silangen, Patricia Mardiana; Tumimomor, Farly Reynol; Tumangkeng, Jeane Vera; Lolowang, Jimmy (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
Physics learning in university is often theoretical and lacks a contextual approach, making it difficult for students to understand concepts in depth. Thematic-Explorative-Democratic Learning (TED) is an approach that emphasizes the exploration of real experiences and democratic interaction. This study aims to determine the results of physics concept exploration and democratic interaction of students through the application of TED learning themed traditional games cenge-cenge. The research method used is descriptive qualitative with data collection techniques through observation, exploration sheets, and democratic interaction assessment sheets. The results show that students are able to identify various physics concepts such as Newton's laws, gravity, parabolic motion, rigid body equilibrium, friction, and momentum. Democratic interaction is seen from active collaboration between students across semesters. It is concluded that TED learning based on traditional games is effective in improving contextual physics understanding as well as student participation and cooperation.